Assessment of microfinance groups in Myanmar - Tun Tun Naing; Ahmad, Mokbul Morshed; Routray, Jayant Kumar; Soparth Pongquan; World Bank (JJ/WBGSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2011)
Rural poor people always need financial service, and be sure to take loan from informal money lenders with higher interest rates unless microfinance service has engaged them within their program. However, every poor cannot access to money lenders due to the lack of collateral to give and this leads to a long term threat to enhance productivity of local business and development process across the country. This study focuses on the microfinance groups in Myanmar, particularly in the delta region in which many people rehabilitated their livelihoods with the help of microfinance service after a severe Cyclone Nargis struck. Data collection was done with both primary and secondary in the specific study area of Labutta Township. This paper analyzed two units of individual and groups, using quantitative and qualitative. Many microfinance members improved their socioeconomic conditions under the microfinance project while some members seemed not to improve due to the misused of Joan util ization, and particularly conflict among the members was taken place. Group performance enhanced the local institutions' capacity, such as members involved in the local CBOs to participate in any activities of village affairs. However, group solidarity is related to the intervention of microfinance program, and it is not sure to be sustainable if the microfinance service is withdrawing its service in the future. Since there has not been a specific financial institutions law for microfinance, it is difficult to be institutionalized for strengthening future projects.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Regional and Rural Development Planning, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2011
Keywords: Microfinance -- Evaluation -- Myanmar